2021
DOI: 10.1113/ep089820
|View full text |Cite
|
Sign up to set email alerts
|

Altered central and peripheral haemodynamics during rhythmic handgrip exercise in young adults with SARS‐CoV‐2

Abstract:  What is the central question of this study?This study sought to investigate whether central and peripheral hemodynamics during handgrip exercise were different in young adults 3-4 weeks following infection with of SARS-CoV-2 compared with young healthy adults. What is the main finding and its importance?The main findings are that exercising heart rate was higher while brachial artery blood flow and vascular conductance were lower in the SARS-CoV-2 compared with the control group. These findings provide evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 93 publications
0
22
0
Order By: Relevance
“…Subjects tested positive for SARS-CoV-2 using a nasopharyngeal swab polymerase chain reaction (PCR) assay 3–4 wk before study inclusion. The current investigation includes subjects from previously published studies ( 2 , 3 , 7 , 13 ) but all data presented are new to this investigation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects tested positive for SARS-CoV-2 using a nasopharyngeal swab polymerase chain reaction (PCR) assay 3–4 wk before study inclusion. The current investigation includes subjects from previously published studies ( 2 , 3 , 7 , 13 ) but all data presented are new to this investigation.…”
Section: Methodsmentioning
confidence: 99%
“…Our group has previously provided evidence of vascular dysfunction ( 3 ) and elevated arterial stiffness ( 2 , 3 ) among young adults 3–4 wk following infection with SARS-CoV-2. These data included significantly attenuated responses to brachial artery flow-mediated dilation, hyperemic response to passive limb movement, and brachial artery blood flow during handgrip exercise, in addition to elevated carotid-femoral pulse wave velocity (cfPWV) in young adults with SARS-CoV-2 compared with healthy controls ( 3 , 13 ). Similarly, Schnaubelt et al ( 14 ) observed elevated cfPWV 1 mo after infection with SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we and others have previously shown that COVID-19 resulted in reduced endothelial function indicated by decreased flow-mediated dilation (FMD) ( 3 5 ), impaired microvascular reactivity (i.e., blunted reactive hyperemia) ( 3 , 4 ), and increased arterial stiffness ( 3 , 6 ). Furthermore, persons with COVID-19 were also shown to have potential impairments in cardiovascular autonomic function with elevated muscle sympathetic nervous system activity ( 7 ) and reduced blood flow responses to exercise ( 8 ). Collectively, these findings suggest that COVID-19 negatively influences the cardiovascular and autonomic nervous system in young, otherwise healthy adults, which may result in increased cardiovascular disease risk in this population ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Circulating proinflammatory mediators can also cross the blood-brain barrier and directly activate the sympathetic nervous system (SNS) and/or trigger peripheral receptors stimulating group III/IV afferent feedback, ultimately resulting in exaggerated SNS activity. Interestingly, in young adults ∼1 mo post-SARS-CoV-2 infection, SNS activity was heightened at rest ( 56 ) and the exercise pressor response (elevated heart rate and systolic blood pressure) was exaggerated during isometric handgrip exercise ( 57 ). Taken together, this suggests that impaired autonomic regulation following COVID-19 infection contributes to altered hemodynamics and vascular abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…5 ). The large decrease in DO 2 highlights the importance of peripheral factors such as impaired hemodynamics ( 57 ), lower hematocrit ( 66 ), and capillary density, along with altered skeletal muscle metabolism in limiting exercise tolerance in COVID-19 survivors.…”
Section: Introductionmentioning
confidence: 99%